Multi-stage and multi-attribute risk group decision-making method based on grey information. Issue 2 (3rd August 2015) - Luo, Dang; Li, Yuwen
Abstract : Purpose: – For the multi-stage and multi-attribute risk group decision-making problem, the attribute weight, decision-maker weight and time weight are unknown. The attribute value is grey information. The purpose of this paper is to discuss a decision-making method. Design/methodology/approach: – Analysis techniques and the theory about distance degree are used to determine the decision-maker weight within single stage. Grey relational analysis method is applied to determine the attribute weight. Moreover, the uncertainty of time weight and the proximity between the attribute value and positive/negative value are taken into account. A multi-objective optimization model is established based on maximum entropy to obtain time weights, so the comprehensive value is determined. Findings: – An example shows the effectiveness and practicability. Originality/value: – For a decision-making process, the results are different in different periods. This method is computationally very simple, easily comprehensible.